The influence of personality dimensions on material and frugal values - Puente-Diaz, Rogelio; Cavazos Arroyo, Judith (Anales de Psicología / Annals of Psychology, 2014)
Two studies were conducted to examine the influence of personality dimensions on material and frugal values and the affective and cognitive consequences of holding these values among college students from Mexico. Participants completed a battery of questionnaires. Structural Equation Modeling (SEM) was used to test the hypothesized relations between personality dimensions, material and frugal values, life and financial satisfaction, and positive and negative affect. Results showed that extraversion had a positive influence of materialism and a negative influence of frugality. Similarly, agreeableness was negatively related to materialism and positively related to frugality. Conscientiousness also had a positive effect on frugality. Lastly, our results showed that materialism was negatively related to positive affect and life and financial satisfaction. Our discussion centered on understanding the interplay between core components of each personality dimension and the defining features of material and frugal values.